Cancer Stem Cells in Oral Cavity Squamous Cell Carcinoma: A Review - Baillie, Ranui; Tan, Swee T.; Itinteang, Tinte (Frontiers in Oncology, 2017)
Cancer stem cells (CSCs) have been identified in oral cavity squamous cell carcinoma (OCSCC). CSCs possess the ability for perpetual self-renewal and proliferation, producing downstream progenitor cells and cancer cells that drive tumor growth. Studies of many cancer types including OCSCC have identified CSCs using specific markers, but it is still unclear as to where in the stem cell hierarchy these markers fall. This is compounded further by the presence of multiple CSC subtypes within OCSCC, making investigation reliant on the use of multiple markers. This review examines the current knowledge in CSC markers OCT4, SOX2, NANOG, ALDH1, pSTAT3, CD44, CD24, CD133, MUSASHI-1, specifically focusing on their use and validity in OCSCC CSC research and how they may be organized into the CSC hierarchy. OCSCC CSCs also express components of the renin-angiotensin system (RAS), which suggests CSCs may be novel therapeutic targets by modulation of the RAS using existing medications.